Personal, portable, pedestrian : mobile phones in Japanese life - Itō, Mizuko; Okabe, Daisuke; Matsuda, Misa, 1968- (MIT Press, 2005)
The Japanese term for mobile phone, keitai (roughly translated as "something you carry with you"), evokes not technical capability or freedom of movement but intimacy and portability, defining a personal accessory that allows constant social connection. Japan's enthusiastic engagement with mobile technology has become -- along with anime, manga, and sushi -- part of its trendsetting popular culture. Personal, Portable, Pedestrian, the first book-length English-language treatment of mobile communication use in Japan, covers the transformation of keitai from business tool to personal device for communication and play. The essays in this groundbreaking collection document the emergence, incorporation, and domestication of mobile communications in a wide range of social practices and institutions. The book first considers the social, cultural, and historical context of keitai development, including its beginnings in youth pager use in the early 1990s. It then discusses the virtually seamless integration of keitai use into everyday life, contrasting it to the more escapist character of Internet use on the PC. Other essays suggest that the use of mobile communication reinforces ties between close friends and family, producing "tele-cocooning" by tight-knit social groups. The book also discusses mobile phone manners and examines keitai use by copier technicians, multitasking housewives, and school children. Personal, Portable, Pedestrian describes a mobile universe in which networked relations are a pervasive and persistent fixture of everyday life